Once upon a time I lived on Mars : space, exploration, and life on earth - Greene, Kate, 1979- (St. Martin's Press, 2020)
When it comes to Mars, the focus is often on how to get there: the rockets, the engines, the fuel. But upon arrival, what will it actually be like? In 2013, Kate Greene moved to Mars. That is, along with five fellow crew members, she embarked on NASA's first HI-SEAS mission, a simulated Martian environment located on the slopes of Mauna Loa in Hawai'i. For four months she lived, worked, and slept in an isolated geodesic dome, conducting a sleep study on her crew mates and gaining incredible insight into human behavior in tight quarters, as well as the nature of boredom, dreams, and isolation that arise amidst the promise of scientific progress and glory. In Once Upon a Time I Lived on Mars, Greene draws on her experience to contemplate humanity's broader impulse to explore. The result is a twined story of space and life, of the standard, able-bodied astronaut and Greene's brother's disability, of the lag time of interplanetary correspondences and the challenges of a long-distance marriage, of freeze-dried egg powder and fresh pineapple, of departure and return. By asking what kind of wisdom humanity might take to Mars and elsewhere in the Universe, Greene has written a remarkable, wide-ranging examination of our time in space right now, as a pre-Mars species, poised on the edge, readying for launch.